Different Carapace Asymmetry Among Sexes in Vulnerable Tortoise: Chelonoidis carbonarius Spix 1824 (Testudines: Testudinidae) - Salamanca-Carreño, Arcesio; Parés-Casanova, Pere M.; Pinzón-Guzmán, Brando E.; Díaz-Caviedes, Daniel A. (Bogor Agricultural University, Indonesia, 2025)
Developmental stability (DS) is characterized by an individual's ability to resist random environmental and/or genetic perturbations during their development. Fluctuating Asymmetry (FA) is the most common means of assessing developmental stability (DS) in bilateral traits. To date, little attention has been paid to sexual differences in FA among tortoises. The aim was to assess the levels of carapace scutation symmetries in a sample of 45 wild adult red-footed tortoises, Chelonoidis carbonarius (13 males and 32 females), from the Arauca plains (Colombia) using geometric morphometric techniques. The landmark configuration, based on the dorsal scute sutures of the carapace, consisted of 7 symmetric pairs with three landmarks along the axial plane, and was tested. Procrustes ANOVA reflected sex-related FA (p<0.05), with males tending to exhibit a more pronounced asymmetry. Although we cannot identify the potential sources responsible for the detected developmental instability, our results suggest a high degree of stress and highlight that human intervention in Arauca is affecting wildlife. Similar studies in the future, correlated with an estimate of human impact, could provide irrefutable proof of causality between FA and environmental stressors. The results of this study may represent an estimate of the physical status of the Chelonoidis carbonarius (Spix 1824) population currently being studied.